Gerakan Politik Agraria oleh Petani di Indonesia (Studi pada Serikat Petani Indonesia) - Randa Putra Kasea Sinaga; Fajar Utama Ritonga; Andry Anshari (Politeia: Jurnal Ilmu Politik, 2023)
Based on the transformation of the agrarian struggle into a political movement carried out by Serikat Petani Indonesia (SPI) as a mass peasant organization over the problem of inequality in agrarian control in Indonesia, this paper describes and analyzes how the pattern of agrarian political movements is carried out. By using data collection techniques such as literature studies and in-depth interviews at the SPI management level (from the base level in the village sector; the regional level in the provincial sector, as well as the central level in charge of the national and international sectors).By using the Narrative Research Analysis approach, the authors classify the patterns of political movements carried out by SPI, classified into local, national and international levels, each level having links as a pattern that is deemed necessary to synergize with each levels. SPI has taken actions from a social, economic, cultural, and political standpoint that are manifestations of views based on problems faced by peasants themselves. Based on the findings of this study, the authors believe that agrarian issues necessitate a massive multi-dimensional political movement that is justly oriented toward the interests of the people.